2011
DOI: 10.1016/j.jnci.2011.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of fine needle aspiration cytology (FNAC) as a diagnostic tool in cases of cervical lymphadenopathy

Abstract: The overall diagnostic accuracy of FNAC of cervical lymph nodes was 82.2% while the overall discordance rate was 17.8%. The evaluation of FNA in patients with no previously diagnosed malignancy should be interpreted by an experienced cytopathologist in the context of clinical, radiological, and laboratory finding and if any of these findings is suspicious, further investigation is justified to overcome the limitations and pitfalls of the cytomorphological features when applied alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
72
3
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 22 publications
(28 reference statements)
20
72
3
1
Order By: Relevance
“…In the present study, SCC was the most common metastatic tumor followed by adenocarcinoma and poorly differentiated carcinoma. Similar findings were reported in other studies (Ahmad et al, 2005;Khajuria et al, 2006;Hafez et al, 2011). In contrast, other study (Ghartimagar et al, 2011) found adenocarcinoma to be the most common tumor to metastize lymph nodes followed by SCC.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, SCC was the most common metastatic tumor followed by adenocarcinoma and poorly differentiated carcinoma. Similar findings were reported in other studies (Ahmad et al, 2005;Khajuria et al, 2006;Hafez et al, 2011). In contrast, other study (Ghartimagar et al, 2011) found adenocarcinoma to be the most common tumor to metastize lymph nodes followed by SCC.…”
Section: Discussionsupporting
confidence: 89%
“…The value of FNAC besides making a diagnosis also lies in early direction of appropriate investigations (Khajuria et al, 2006). The frequency of metastatic lymphadenopathy was observed to be low, 3.8% and 8.7% in some studies (Khajuria et al, 2006;Fatima et al, 2011) whereas, a higher incidence of 19.7 % and 24.7% was reported by other studies (Hafez et al, 2011, Ageep et al, 2012 respectively. However, in the current study, metastatic lymphadenopathy contributed to 31.3% of lymphadenopathies.…”
Section: Discussionmentioning
confidence: 88%
“…CLN enlargement includes a certain frequency of various types of malignant disease. The percentages of patients with malignant disease in reports that analyzed FNA cytology of CLN ranges from 46% to 69.4% 7, 11, 23. Our combined results of CS cytology and LBC showed a similar rate of 50.1% of 165 patients analyzed with malignant disease.…”
Section: Discussionmentioning
confidence: 99%
“…FNAC of lymph node has become an integral part of the initial diagnosis and management of patients with lymphadenopathy due to early availability of results, simplicity, and, minimal trauma with less complication. FNAC has also been advocated as a useful method in comparison to more expensive surgical excision biopsies in developing countries with limited financial and health care resources (Hafez et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the commonest and significant clinical presentations of patients, attending the outdoor clinics in most hospitals. The aetiology varies from an inflammatory process to a malignant condition (Hafez et al, 2011). For assessment of lymphadenopathy, different modalities are used which include FNAC, automatic core needle biopsy, flow cytometry, radiologically guided core needle biopsy and open biopsy.…”
Section: Introductionmentioning
confidence: 99%